The Impact of 2014 Olympic Games on Sochi Tourism Life Cycle - ALEXANDROVA, Anna Yu.; AIGINA, Ekaterina V.; MINENKOVA, Vera V. (Journal of Environmental Management and Tourism; Vol 10 No 6 (2019): JEMT Volume X Issue 6(38) Fall 2019, 2019)
Sochi is a unique destination. The combination of the Caucasus and the Black Sea gives the opportunity to develop winter recreation in the mountains and summer activities in the coastal zone in parallel. Sochi evolved as a spa resort in the beginning of the 1900s and gained its specialization as a health resort for mass tourism in the 1930s. Consolidation and saturation stages took place in the 1970-80s on the rise of domestic tourism when Sochi turned into a year-round resort for seaside recreation. Sochi went through decline stage in the 1990s it but was able to recover when the city of Sochi had the honour to host the Olympic Games in 2014. Now Sochi combines diverse opportunities for tourism development, including events and business tourism. The Sochi Olympics were not just a sporting event. Huge funds spent on preparation for the Games, and the priority of the Russian Government, which was used by the city, were to serve two main purposes: on one hand, to give impulse to regional development, create a modern infrastructure and turn Sochi into a world-famous winter resort and, on the other hand, to present to the whole world a new image of Russia as an open, modern and attractive country. The games were intended to be a catalyst for the development of Sochi as a winter resort and, together with its reputation as a summer holiday destination, turn this area into a year-round tourist destination. The study focuses on the legacy of post-Olympic tourism in Sochi, its preservation, growth and effective work in relation to the life cycle of the tourist zone of Sochi. Historical perspective and field studies, statistical and content analysis supported by in-depth interviews of tourism subjects reveal the key tourism development problems and ways for their solution in the post-Olympic period. Further improvement of the year-round tourism product of Sochi requires additional efforts in marketing promotion, smoothing of seasonal fluctuations, organization of work of the operator company on management of Olympic facilities and expansion of new types of tourism activities.